Answer:
5x^2 − 2x
Step-by-step explanation:
Let's simplify step-by-step.
=3x + 6x^2 + − 5x + − x^2
Combine Like Terms:
=3x + 6x^2 + − 5x + − x^2
=( 6x^2 + − x^2 ) + ( 3x + − 5x )
= 5x^2 + − 2x
Answer:
5x^2 − 2x
hope this helps!!
Answer:
x > 6
Step-by-step explanation:
-5 > 19 - 3x + (-6)
Combine like terms.
-5 > 13 - 3x
Subtract 13 from both sides.
-18 > -3x
Divide both sides by -3.
6 < x
Flip this around. x > 6
Answer:
5
Step-by-step explanation:
Answer:
x = 16
Step-by-step explanation:
Assuming the question is asking to solve for ,
We can translate the statement "three less than x is equal to 13" into:
Thus we can write [as above]
Solving for x gives us:
x is 16
Hi Brar
√3*3*5*5
= 75√3
I hope that's help !
Answer:
Step-by-step explanation:
You have to graph the following equation:
y – 4 = (x + 2)
Lets start by summing 4 in both sides:
y – 4 + 4= (x + 2) + 4
y = (x + 2) + 4
By commutative property we can write that:
y = x + (2 + 4)
y = x + 6
So, our equation can be written as y = x + 6
Now, for drawing the graph we need two points (x1, y1) and (x2, y2)
As the independent term is 6 we know the function passes trough (0, 6). Now we need another point, lets try with some simple. Lets see what happens is x is equal to 1:
y = 1 + 6 = 7
So, the function passes trough (0, 6) and (1, 7). For graphing it we just ned to identify those points in the axis and draw a line that crosses both of them. Here I attach a graph for this.
Answer:
The answer is C. Hope this helps you!
Step-by-step explanation:
1. Plot the point (–2,4).
2. From that point, count left 3 units and down 1 unit and plot a second point.
3. Draw a line through the two points.